A Survey of Small-scale Layer Production Systems in Botswana - Badubi, S.S.; Ravindran, V. (International Journal of Poultry Science, 2004)
A questionnaire-based survey was conducted to investigate small-scale layer production systems in Botswana. The survey covered layer farms in the districts of Francistown and Letlhakane in the eastern part of Botswana, and examined aspects of productivity parameters, housing, management and diseases. The average hen day production in small-scale layer farms was 71.7% and the average daily feed intake was 108.1 g per hen. An average of 1 740 g feed was required to produce one dozen eggs. Hens were culled after 52 weeks in production (around 78 weeks of age). During this period, a hen produced an average of 245 eggs. These productivity levels were well below the standards indicated by the breeding companies. The average mortality from 18 weeks of age to culling was 8.46%. Diseases or conditions reportedly associated with these deaths included Newcastle Disease, prolapse of the uterus and enteritis. Factors responsible for the poor layer performance under small farm conditions in Botswana are clearly complex, but poor managerial skills, irregular feed supply and, poor quality of feed and pullets are major contributing reasons. The lower production levels, however, suggest that there is considerable potential for improvement.